Obstructive Sleep Apnea, Sleepiness, and Glycemic Control in Type 2 Diabetes - Aurora, R. Nisha (J Clin Sleep Med, 2019)
STUDY OBJECTIVES: Self-reported sleepiness is common in patients with obstructive sleep apnea (OSA) and is being increasingly recognized as an effect modifier of the association between OSA and cardiovascular outcomes. However, data on whether sleepiness modifies the association between OSA and glycemic outcomes are lacking. The current study sought to characterize the association between glycemic control and sleepiness in people with OSA and type 2 diabetes. METHODS: Adults with non-insulin requiring type 2 diabetes and undiagnosed moderate to severe OSA were recruited from the community. Demographic data, Epworth Sleepiness Scale (ESS), hemoglobin A1c (HbA1c), as well a type III home sleep test were obtained. The association between self-reported sleepiness and glycemic control was examined using quantile regression. RESULTS: The study cohort included 311 participants with 56% of the sample being men. Stratified analyses by sex demonstrated that self-reported sleepiness was associated with a higher HbA1c level, but this association was present only in men with a body mass index (BMI) < 35 kg/m(2). Mean HbA1c levels were higher by 0.57% (95% confidence interval: 0.11, 1.02) in men with an ESS ≥ 11 compared to men with an ESS < 11. No such association was observed in men with a BMI ≥ 35 kg/m(2) or in women of any BMI category. CONCLUSIONS: The association between self-reported sleepiness and glycemic control in people with type 2 diabetes and moderate to severe OSA varies a function of BMI and sex. The noted differences in association should be considered when assessing possible treatment effects of therapy for OSA on metabolic outcomes. CITATION: Aurora RN, Punjabi NM. Obstructive sleep apnea, sleepiness, and glycemic control in type 2 diabetes. J Clin Sleep Med. 2019;15(5):749–755.